Results from an international multicentre double-blind randomized controlled trial on the perioperative efficacy and safety of bipolar vs monopolar transurethral resection of the prostate - Mamoulakis, Charalampos; Schulze, Michael; Rassweiler, Jens (BJU international, 2012)
Study Type - Therapy (RCT) Level of Evidence 1b What’s known on the subject? and What does the study add? Short-term efficacy is similar but B-TURP is preferable due to a more favourable safety. a) first multicentre RCT, b) adequate quality, c) experience with a new bipolar device, d) morbidity standardize using the modified Clavien classification system. OBJECTIVE • To compare the perioperative efficacy and safety of bipolar (B-) and monopolar transurethral resection of the prostate (M-TURP) in an international multicentre double-blind randomized controlled trial using the bipolar system AUTOCON® II 400 ESU for the first time. PATIENTS AND METHODS • From July 2006 to June 2009, consecutive transurethral resection of the prostate (TURP) candidates with benign prostatic obstruction were prospectively recruited in four academic urological centres, randomized 1:1 into an M-TURP or B-TURP arm and followed up for 6 weeks after surgery. • A total of 295 eligible patients were enrolled. • Of these, 279 patients received treatment (M-TURP, n= 138; B-TURP, n= 141) and were analysed for immediate postoperative outcomes and perioperative safety. In all, 268 patients (M-TURP, n= 129; B-TURP, n= 139) were analysed for efficacy, which was quantified using changes in maximum urinary flow rate, postvoid residual urine volume and International Prostate Symptom Score at 6 weeks compared with baseline. Safety was estimated using sodium and haemoglobin level changes immediately after surgery and perioperative complication occurrence graded according to the modified Clavien classification system. • Secondary outcomes included operation-resection time, resection rate, capsular perforation and catheterization time. RESULTS • No significant differences were detected between each study arm except that postoperative decreases in sodium levels favoured B-TURP (-0.8 vs -2.5 mmol/L, for B-TURP and M-TURP, respectively; P= 0.003). The lowest values were 131 mmol/L (B-TURP) and 106 mmol/L (M-TURP). Nine patients ranged between 125 and 130 mmol/L and the values for three patients were <125 mmol/L after M-TURP. The greatest decrease was 9 mmol/L after B-TURP (two patients). In nine patients (M-TURP) the decrease was between 9 and 34 mmol/L. • These results were not translated into a significant difference in TUR-syndrome rates (1/138: 0.7% vs 0/141: 0.0%, for M-TURP and B-TURP, respectively; P= 0.495). CONCLUSIONS • In contrast to the previous available evidence, no clinical advantage for B-TURP was shown. Perioperative efficacy, safety and secondary outcomes were comparable between study arms. • The potentially improved safety of B-TURP that is attributed to the elimination of dilutional hyponatraemia risk, a risk still present with M-TURP, did not translate into a significant clinical benefit in experienced hands.
First published: 09 May 2011
Gesehen am 17.10.2018